Evaluation of risk factors for metabolic syndrome in epileptic patients in Palembang, Indonesia: a hospital-based and case-control study - Sri Handayani; Radiyati Umi Partan; Zen Hafy; Fitri Octaviana; Diah Widiastuti (Medicinski glasnik, 2025)
Aim: To examine the association between metabolic syndrome and risk factors in epileptic patients at Dr. Mohammad Hoesin General Hospital in Palembang, Indonesia. Methods: A hospital-based comparative case control research was conducted from July to September 2023. A total of 102 patients in the epilepsy group and 102 in the control group participated in this study. We conducted the data collection approach in three stages: a questionnaire, anthropometric measures and biochemical analysis. Results: Epilepsy patients were more likely to develop metabolic syndrome than the controls. The epilepsy group exhibited higher triglycerides, fasting blood sugar, and lower high density lipoprotein (HDL) values than the control group. The epilepsy group exhibited sedentary behaviour, while the control group had moderate to intense physical activity (p<0.05). Epilepsy patients who take polytherapy, or several antiepileptic drugs, were 8.43 times more likely to develop metabolic syndrome (OR=8.43; 95%CI=1.45-32.12). Epilepsy patients with body mass index (BMI) >25 had 1.57 times the risk of metabolic syndrome (OR=1.57; 95%CI=1.16-2.34). Epilepsy patients with total cholesterol levels >200 mg/dL have a 5.81-fold higher risk of metabolic syndrome (OR=5.81; 95%CI=1.23-23.32). Conclusion: Our study found that more than a quarter of epilepsy patients have metabolic syndrome. The main risk factors for metabolic syndrome in epilepsy patients were a sedentary lifestyle, several antiepileptic medications, overweight, and increased total cholesterol levels.
Keywords: anticonvulsants; blood glucose; cholesterol; sedentary behaviour; triglycer-ides